2007
DOI: 10.1093/pcp/pcm036
|View full text |Cite
|
Sign up to set email alerts
|

Bi-Parental Cytoplasmic DNA Inheritance in Wisteria (Fabaceae): Evidence from a Natural Experiment

Abstract: Cytoplasmic inheritance was investigated in interspecific hybrids of Wisteria sinensis and W. floribunda. Species-specific nuclear, mitochondrial and plastid DNA markers were identified from wild-collected plants of each species in its native range. These markers provide evidence for the bi-parental transmission of plastids in hybrid swarms of these two species in the southeastern USA. These population level molecular data corroborate previous cytological evidence of this phenomenon in Wisteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 5 publications
0
19
0
1
Order By: Relevance
“…Nevertheless, the plastid DNA of the inverted repeat lacking clade (IRLC; see Figs 1, 2; also as in Lavin et al 1990; Wojciechowski et al 2000) in Leguminosae was reported to be inherited paternally or biparentally (Zhang et al 2003), confirmed by cytoplasmic and phylogenetic studies focusing on Medicago L. (paternal transmission; Schumann and Hancock 1989; Masoud et al 1990; Havananda et al 2010) and Wisteria Nutt. (Hu et al 2005; Trusty et al 2007). As Chesneya s.s. belongs to IRLC, a paternal inheritance scenario might be the case for the plastid DNA of Chesneya s.s. …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the plastid DNA of the inverted repeat lacking clade (IRLC; see Figs 1, 2; also as in Lavin et al 1990; Wojciechowski et al 2000) in Leguminosae was reported to be inherited paternally or biparentally (Zhang et al 2003), confirmed by cytoplasmic and phylogenetic studies focusing on Medicago L. (paternal transmission; Schumann and Hancock 1989; Masoud et al 1990; Havananda et al 2010) and Wisteria Nutt. (Hu et al 2005; Trusty et al 2007). As Chesneya s.s. belongs to IRLC, a paternal inheritance scenario might be the case for the plastid DNA of Chesneya s.s. …”
Section: Discussionmentioning
confidence: 99%
“…Although it has been traditionally thought that mitochondria exhibit strictly maternal inheritance, recent genetic studies have identified some examples of biparental/paternal mitochondrial inheritance (Erickson and Kemble 1990;Fauré et al 1994;Trusty et al 2007). In the case of species in which mitochondria exhibit biparental inheritance and the plastids exhibit maternal inheritance, organellar DNA in mature generative/sperm cells can only be mitochondrial DNA.…”
Section: Digestion Of Organellar Dna In the Generative Cellmentioning
confidence: 99%
“…Since the early 1990s, restriction fragment length polymorphisms (RFLPs) have been used frequently to obtain specific markers for organellar DNA, and have made it easier to examine mitochondrial and plastid inheritance (Boblenz et al 1990;Derepas and Dulieu 1992;Hu et al 1996;Trusty et al 2007;Hansen et al 2007;Matsushima et al 2008b). Examples of biparental or paternal inheritance of mitochondrial DNA (Erickson and Kemble 1990;Havey 1997;Trusty et al 2007), as well as maternal inheritance (Steinborn et al 1995) have been found using RFLP analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the paternal or biparental inheritance of mitochondrial genomes has been Edited by Toru Terachi * Corresponding author. E-mail: hirokazu@affrc.go.jp Note: Supplementary materials in this article are at http:// www.jstage.jst.go.jp/browse/ggs reported in species such as bananas, cucumber and Wisteria (Faure et al, 1994;Havey, 1997;Trusty et al, 2007), the paternal inheritance of the rapeseed mitochondrial plasmid is completely independent from the inheritance of the main mitochondrial genome, i.e., the plasmid may be inherited paternally even if the mitochondrial genome shows a strict maternal inheritance pattern. Fluorescence microscopy observation has shown that mitochondrial DNA molecules disappear during pollen development in rapeseed (Sato et al, 2004).…”
Section: Introductionmentioning
confidence: 99%